A Bioethical Critique of Short-Term Medical Service Trips - Hamideh, Noor (The Meducator, 2018)
Short-term Medical service trips (MSTs) involve students with minimal medical training travelling abroad to gain healthcare experience and improve the health of the host community (HC). They have become increasingly popular in the United States and Canada, with approximately one third of medical graduates having completed a MST. MSTs are marketed as both charitable missions and experiential learning opportunities. Because these trips are seen as an act of charity, their ethical implications are often left unexamined. However, many practices involved in MSTs may directly oppose the principles of biomedical ethics. Due to communication barriers and the inherent power differential between volunteers and patients, volunteers may undermine the autonomy of patients. Additionally, although volunteers have the intention to benefit patients, their lack of training may lead them to inadvertently harm patients. Finally, the short-term nature of many MSTs, and the pressures they place on host countries may reinforce barriers to global healthcare equity. This essay argues that MSTs should not be considered inherently ethical, but rather that they deserve careful critique.